Breathing in the Cold: Seasonal Changes in the Ventilatory Pattern in a Small Boreal Passerine Bird - Bech, Claus; Mariussen, Carita (Frontiers in Ecology and Evolution, 2022)
Small passerine birds in the north need to take advantage of several behavioural and physiological mechanisms to maintain energy balance during the winter characterized by low food supply, low ambient temperatures, and short days. Here we test if the breathing pattern of a non-migratory species, the great tit (Parus major), show seasonal variation that could help the species keeping a positive energy balance in the winter. To this aim, we measured oxygen consumption and ventilatory variables (tidal volume and respiratory frequency) in summer- and winter-acclimatized great tits exposed to ambient temperatures between -15 and 30°C. Winter-acclimatized great tits had a higher resting metabolic rate and a different breathing pattern compared to the summer-acclimatized birds. During the winter the great tits utilised a breathing pattern, consisting of an increased respiratory frequency to tidal volume ratio compared to summer-acclimatized birds at all temperatures. The higher oxygen uptake and the altered breathing pattern in the winter-acclimatized tits resulted in a higher lung oxygen extraction. However, during acute cold exposure neither the winter- nor summer-acclimatized great tits increased the oxygen extraction at low ambient temperature. The higher lung oxygen extraction in the winter-acclimatized tits implies that the birds will save on the minute ventilation, which reduces the evaporative water loss through respiration. The daily water loss saved can be more than one gram of water per day. This is a substantial saving corresponding to a saving in evaporative heat loss corresponding to between 4 and 8% of the resting metabolic rate. This might be significant in keeping an energy balance, and the altered breathing pattern in the winter, ensuring an increased oxygen extraction, may therefore represents an additional physiological mechanism making it possible for small passerine birds to survive the northern winter.